Incidence and Management of Thrombotic and Thromboembolic Complications Following the Superior Cavopulmonary Anastomosis Procedure: A Literature Review. (April 2018) - Agarwal, Arnav; Firdouse, Mohammed; Brar, Nishaan; Yang, Andy; Lambiris, Panos; Chan, Anthony K.; Mondal, Tapas Kumar
The objective of this literature review was to estimate the incidence of thrombosis and thromboembolism associated with the superior cavopulmonary anastomosis (SCPA) procedure and its variants and to examine current thromboprophylaxis regimens utilized. MEDLINE and EMBASE were searched from inception to August 2017 for all prospective and retrospective cohort studies explicitly reporting incidence of thrombosis, thromboembolism, or shunt occlusion in neonates, infants, and children undergoing 1 or more variants of the SCPA procedure. End points included thrombotic events and thromboembolic events (strokes and pulmonary embolisms) as primary outcomes, and overall mortality as a secondary outcome, at the last available follow-up time point. Of 1303 unique references identified, 13 cohort studies were deemed eligible. Reported incidence of thrombosis and thromboembolic events ranged from 0% to 28.0% and from 0% to 12.5%, respectively. Reported incidence of major bleeding events ranged from 0% to 2.9%. Reported overall mortality ranged from 2.5% to 50.5% across studies. Thromboprophylaxis protocols varied across institutions and studies, most commonly involving unfractionated heparin (UFH), warfarin, enoxaparin, acetylsalicylic acid (ASA), or combinations of ASA and warfarin, ASA and low-molecular-weight heparin (LMWH), UFH and LMWH, and UFH and ASA; several studies did not specify a protocol. Due to substantial variability in reported event rates, no clear correlation was identified between prophylaxis protocols and postoperative thrombotic complications. Despite guidance recommending postoperative UFH as standard practice, thromboprophylaxis protocols varied across institutions and studies. More robust trials evaluating different thromboprophylaxis regimens for the management of these patients are warranted.